2020
DOI: 10.3390/genes11020234
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Basis of Natural Variation in Drosophila melanogaster Immune Defense against Enterococcus faecalis

Abstract: Dissecting the genetic basis of natural variation in disease response in hosts provides insights into the coevolutionary dynamics of host-pathogen interactions. Here, a genome-wide association study of Drosophila melanogaster survival after infection with the Gram-positive entomopathogenic bacterium Enterococcus faecalis is reported. There was considerable variation in defense against E. faecalis infection among inbred lines of the Drosophila Genetics Reference Panel. We identified single nucleotide polymorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 73 publications
(99 reference statements)
0
26
1
Order By: Relevance
“…Indeed, several genes have been identified by genome-wide association studies on E. faecalis and entomopathogenic fungi (Chapman et al, 2020;Wang et al, 2017).In addition, we did not observe any protection conferred by the transgenic overexpression of BaraA, in wild-type or MyD88 background. It is thus likely that BaraA acts in conjunction with other Toll pathwayinduced genes.…”
Section: Is Baraa Acting Alone In Host Defense?contrasting
confidence: 61%
See 1 more Smart Citation
“…Indeed, several genes have been identified by genome-wide association studies on E. faecalis and entomopathogenic fungi (Chapman et al, 2020;Wang et al, 2017).In addition, we did not observe any protection conferred by the transgenic overexpression of BaraA, in wild-type or MyD88 background. It is thus likely that BaraA acts in conjunction with other Toll pathwayinduced genes.…”
Section: Is Baraa Acting Alone In Host Defense?contrasting
confidence: 61%
“…Interestingly, this protein appears to be involved both in resistance, through the stabilization of BomS peptides in the hemolymph and in resilience, because of a detrimental effect of BomS peptides in its absence. Finally, flies for which the expression of BomBc1 is attenuated by RNAi have been reported to be sensitive to E. faecalis infection (Chapman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…While C. burnetii is not a natural D. melanogaster pathogen, there is evidence that it is an endosymbiont of tick arthropods and may have co-evolved in these animals ( Duron et al 2015 ). Previous studies show that few genome-wide significant variants are identified when using a non-natural versus natural D. melanogaster pathogen ( Magwire et al 2012 ), or when the pathogen has low prevalence in D. melanogaster ( Chapman et al 2020 ). Similarly, our GWA analyses did not identify any variants that met the expected Bonferonni-corrected P -value significance level.…”
Section: Discussionmentioning
confidence: 99%
“…These bacteria are reported to be extracted from Drosophila melanogaster and are considered as a natural pathogen for the fruit flies [ 29 , 30 ]. A day before infections, primary culture was set up by inoculating a small amount of bacterial inoculum from a cryovial into 10 mL of LB medium.…”
Section: Methodsmentioning
confidence: 99%
“…Larvae from both the regimes were grown at high and low larval densities, and we subsequently measured their survivorship post infection in adult stage with either a gram-negative bacterium Pseudomonas entomophila or a gram-positive bacterium Enterococcus faecalis . Along with causing severe damage to the gut, both the bacteria are known to cause systemic pathogenic infection [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%